Hubungan antara Status Gizi Ibu dengan Berat Lahir Bayi pada Kehamilan Remaja - Syafril Fahmi Hidayat; Rina Pratiwi; Putri Sekar Wiyati (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Teenage pregnancy is prone to cause problems on maternal nutritional status. If nutritional status during pregnancy is not monitored properly, the chance for the mother to experience complications in the birth weight of the newborn can be increased.Objective: To find out the relationship between maternal nutritional status and other risk factors with neonatal birth weight in teenage pregnancy.Methods: This research is an observational analytic study with cross-sectional approach. The samples of this study were collected by consecutive sampling from 2019 to December 2021 using secondary data of RSUP Dr. Kariadi Semarang. The data were analyzed by using chi-square, fisher’s exact and mann-whitney test.Result: The results showed that there were significant relationships between maternal nutritional status (p=0.001), gestational age (p<0.001), abortion history (p=0.045), anemia status (p=0.019), and multiple pregnancy (p=0,035) with neonatal birth weight. Meanwhile, the variables of maternal age, education, occupation, gravidity, diabetes melitus, hypertension, preeclampsia, prelabor rupture of the membranes, and antepartum haemorrhage did not have a significant relationship with neonatal birth weight.Conclusion: There is significant relationships between maternal nutritional status, gestational age, abortion history, anemia status, and multiple pregnancy with neonatal birthweight  Keywords:  maternal nutritional status, birth weight, teenage pregnancy